Fashion-design in the conditions of information flows asymmetry of fashion industry - Gardabkhadze, I. (Theory and practice of design, 2017)
Asymmetry of information on the fashion market leads to a problem of deteriorating selection of fashion products, which negatively affects the sustainable development of the fashion industry. The article is devoted to actual problem of analysis the features of design creativity in the conditions of goods selection deterioration in the fashion industry market. It is shown that the influence of information asymmetry on fashion lies in accelerating in its trends change and in the growth of supplies to the fashion market of Ukraine of low quality "no name" goods by "gray dealers" and "copywriters" of fashion world. The scientific novelty consists in the approach to adaptation of design processes to new requirements, generated by information asymmetry of fashion market . For the first time to compensate for information asymmetry in the fashion market, it was suggested to implement two actions:- by initializing new and upgrading existing channels of communication between fashion designers, manufacturers, suppliers and target groups of consumers; and - by means of expanding the scope of the fashion designers’ competencies in the methods of individualizing the project activity and by improving a skills in using network tools of interactive collaboration with consumers.